SPONGIOTIC DERMATITIS WITH A MIXED INFLAMMATORY INFILTRATE OF LYMPHOCYTES, ANTIGEN PRESENTING CELLS, IMMUNOGLOBULINS AND COMPLEMENT - Abreu Velez Ana Maria; Loebel Anne M.; Howard Michael S. (Our Dermatology Online, 2011)
Background: The clinical and histological presentation of spongiotic dermatitis and its inflammatory infiltrates warrant further investigation. In this case documentation of a patient with cutaneous spongiotic reactivity, we aim to characterize antigen presenting cells, as well as the skin-specific cutaneous lymphocyte antigen population by multiple techniques. Case report: A 30 year old Caucasian female presented with a two week history of blistering and erosions around the vaginal, rectal and axillary areas. Material and Methods: We utilized hematoxylin and eosin histology, direct immunofluorescence, immunohistochemistry and confocal microscopy methods to evaluate the immune reaction patterns of the cutaneous inflammatory cells. Results: In the primary histologic areas of spongiotic dermatitis, a mixed population of B and T lymphocytes was seen. Ki-67 antigen proliferative index staining was accentuated in these areas, correlating with the presence of large numbers of epidermal and dermal antigen presenting cells. Among the antigen presenting cell population, we detected strong positivities with CD1a, Factor XIIIa, myeloid/hystoid antigen, S100, HAM-56, and CD68. Interestingly, immunoglobulins G, D and M and Complement factors C1q and C3 were also strongly expressed in antigen presenting cell areas, including positivity within the spongiotic epidermis and around dermal vessels. Conclusions: We document a heterogeneous population of B and T lymphocytes and the presence of multiple classes of antigen presenting cells, immunoglobulins and complement in and surrounding histologically spongiotic areas; these findings further correlated with increased levels of expression of Ki-67.